Analysis of evaluations performed by undergraduate nursing alumni: a Brazilian multicenter study* - Aguiar, Katiuscia Larsen de Abreu; Vieira, Maria Aparecida; Domenico, Edvane Birelo Lopes de (Revista da Escola de Enfermagem da USP, 2021)
Objective: To compare evaluations performed by undergraduate nursing alumni in three dimensions: sociodemographic characterization, identification and insertion into the job market, and professional training evaluation. Methods: Cross-sectional, quantitative, and multicenter study with alumni of three Brazilian public institutions. Data analysis was carried out according to the internal reliability of the used instrument and by applying descriptive statistics. Results: The participants were 446 alumni who obtained their degrees from 2013 to 2016. Most were women, white (44%) or brown (38%), and were between 25 and 30 years old. Most had a specialization degree or were studying to obtain one (54%), had a paid occupation (89%), and were employed by a single institution (60%), with the care area prevailing (57%) in the sample. High levels of satisfaction were found among alumni of two institutions in the evaluation of content learning and essential experiences for training, whereas the other institution obtained better evaluations regarding professional practice. Conclusion: The profile of academic experiences, graduate education, and entry into the job market varied according to the evaluated institution. The findings favored critical-reflective analysis of the institutions’ pedagogical projects.